2008
DOI: 10.2459/jcm.0b013e328058680b
|View full text |Cite
|
Sign up to set email alerts
|

Differences between diabetic and non-diabetic hypertensive patients with first acute non-ST elevation myocardial infarction and predictors of in-hospital complications

Abstract: This study indicates that in-hospital complications, including heart failure and transient cerebral ischaemia, occur frequently during the acute phase of a first NSTEMI in patients with both diabetes and hypertension. The coexistence of diabetes and hypertension doubles the risk of complications with respect to hypertension alone. In addition, adverse events may appear despite an initial uncomplicated clinical presentation, which can be predicted by the early assessment of heart rate and blood pressure behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…No statistically significant (p>0.05) difference was observed between two groups. This is consistent with the study conducted by Colivicchi et al (2008) where that mean age of diabetic patients was 54±2 years and of non-diabetic patients was 56±5 years 5 . The present observation is also similar to a study done in Bangladesh by Salim et al (2015) which revealed that mean age was 58.7 ± 10.7 years in diabetic patients and 57.3 ± 13.2 years in non-diabetic patients with no statistically significant difference 15 .…”
Section: Table-vii Univariate Logistic Regression Analysis Showing Od...supporting
confidence: 93%
See 1 more Smart Citation
“…No statistically significant (p>0.05) difference was observed between two groups. This is consistent with the study conducted by Colivicchi et al (2008) where that mean age of diabetic patients was 54±2 years and of non-diabetic patients was 56±5 years 5 . The present observation is also similar to a study done in Bangladesh by Salim et al (2015) which revealed that mean age was 58.7 ± 10.7 years in diabetic patients and 57.3 ± 13.2 years in non-diabetic patients with no statistically significant difference 15 .…”
Section: Table-vii Univariate Logistic Regression Analysis Showing Od...supporting
confidence: 93%
“…This association has a negative impact on prognosis by strongly predisposing the individual patient to the development of an accelerated atherosclerotic cardiovascular disease. Consequently, diabetic hypertensive subjects have a higher incidence of coronary artery disease than patients with diabetes or hypertension alone 5 . Patients with diabetes who develop a NSTEMI are at increased risk for each hospital outcome including heart failure, renal failure, cardiogenic shock and death 6 .…”
Section: Introductionmentioning
confidence: 99%
“…There is a general agreement that coexistence of diabetes and hypertension is associated with a higher cardiovascular risk and mortality in humans (Endemann et al. 2004; Colivicchi et al. 2008) and animal models (Hendriks et al.…”
mentioning
confidence: 99%
“…In addition, 87.2% of African-American subjects with obesity and high-blood pressure exhibited insulin-resistance (Campbell et al 2004). There is a general agreement that coexistence of diabetes and hypertension is associated with a higher cardiovascular risk and mortality in humans (Endemann et al 2004;Colivicchi et al 2008) and animal models (Hendriks et al 1993;Ballo et al 2010).…”
mentioning
confidence: 99%